2002
DOI: 10.1002/marc.200290009
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Chain‐Particles of Poly(N‐isopropylacrylamide)

Abstract: Spherical single‐chain‐particles of poly(N‐isopropylacrylamide) were prepared in aqueous solution above the lower critical solution temperature upon the addition of sodium dodecyl sulfate. The size of the single‐chain‐particles was investigated by means of transmission electron microscopy and viscosity measurements of the corresponding solutions, indicating the absence of inter‐chain entanglements among the single‐chain‐particles. Schematic of the preparation of PNIPAM single‐chain‐globules in solution.magnifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…This complex model was consistent with the previously proposed pearl-necklace-like complex structure of polymer and surfactant. , The cross-peaks indicated that the charged SDS molecules were in close proximity (<0.5 nm) to the polymer chains, which endows polyelectrolytic characteristics to the complexes of PNIPAM and SDS. Consequently, the hydrodynamic size of PNIPAM in the presence of SDS for intrachain electrostatic repulsion increased compared with that in surfactant-free solution, as also observed by previous studies. , On the other hand, the interchain electrostatic repulsions inhibited the interchain aggregation above the LCST to obtain the PNIPAM single-chain compact globule. , …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This complex model was consistent with the previously proposed pearl-necklace-like complex structure of polymer and surfactant. , The cross-peaks indicated that the charged SDS molecules were in close proximity (<0.5 nm) to the polymer chains, which endows polyelectrolytic characteristics to the complexes of PNIPAM and SDS. Consequently, the hydrodynamic size of PNIPAM in the presence of SDS for intrachain electrostatic repulsion increased compared with that in surfactant-free solution, as also observed by previous studies. , On the other hand, the interchain electrostatic repulsions inhibited the interchain aggregation above the LCST to obtain the PNIPAM single-chain compact globule. , …”
Section: Resultssupporting
confidence: 81%
“…15,16 On the other hand, the interchain electrostatic repulsions inhibited the interchain aggregation above the LCST to obtain the PNIPAM single-chain compact globule. 31,32 In terms of the intensity changes of the cross-peaks with the SDS concentration, the signals of Pa−S2, Pa−S3, and Pa−S4 were obviously stronger with increased SDS concentration. To analyze the 2D NOESY spectra further, 1D spectra extracted from the Pa signal of the 2D NOESY spectra at 1.0 ppm are listed on the right side of each set in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the interchain electrostatic repulsions inhibit the interchain aggregation so that the PNIPAM single-chain compact globule can be obtained. 27,28 However, the noticeable change in the 2D NOESY spectra in Figure 3 shows the decrease in the signal intensity of the crosspeaks between PNIPAM and SDS with increasing temperature, although nearly half of the PNIPAM units are undetected in the NMR spectra above the LCST. Slice 1D spectra were extracted from the 2D NOESY spectra and are shown in the right list of Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] In the study of Hu et al. [ 28 ] no inter‐chain entanglement was found in the single‐chain polymer particles, showing the solution process as a general method to achieve the disentangled polymers.…”
Section: Control Of Polymer Chain Entanglementmentioning
confidence: 99%